Muslims in Nationalist China - Gowing, Peter G. (Silliman Journal, 2024)
Other than two brief pamphlets issued in Taiwan, there is virtually no description of the Taiwan Muslims available in English. This article represents, therefore, an important contribution to knowledge about Taiwan Muslims. There are some 20,000 Muslims on Taiwan, forming an extension in exile of their more than 20 million Muslim brothers under Communist rule on the mainland. Most of the Taiwan Muslims are soldiers or government employees, shopkeepers and teachers. Practically all belong to the middle or lower class and are anti-Communist. They have their problems as a minority religion in a secular society.and their future is uncertain.